Migrant diversity, migration motivations and early integration: the case of Poles in Germany, the Netherlands, London and Dublin - Renee Luthra; Lucinda Platt; Justyna Salamońska (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2014)
The expansion of the European Union eastwards in 2004, with an ensuing massive increase in East-West migration from the accession countries has been represented as a new migration system of a kind unique in recent migration history, with its specific features of rights of movement and low mobility and information costs accompanying persistent East-West wage differentials. In principle, it provides an ideal context in which to develop understandings of the 'new migration' reflecting complex motivations and migration trajectories as well as chain migration and transnational lives. Despite a rapid expansion of research in this area, new insights into the complexities of mixed migration motivations and migrant heterogeneity have tended to be focused on country-specific qualitative studies. In this paper we utilise a unique, four-country data source covering over 3,500 Poles migrating to Germany, the Netherlands, London and Dublin in 2009-2010, to enable the quantitative characterization of the new migration. Exploiting information on pre-migration experience as well as expressed migration motivations and post-migration structural, subjective and social measures of integration in the receiving country, we conduct a three-stage analysis. First we employ latent class analysis to allocate the migrants to six migrant types. Second, we link these migrant types to pre-migration characteristics and estimate multinomial logit models for class membership. Third, controlling for these pre-migration characteristics we are able to explore how the migrant types are associated with measures of integration. We reveal substantial heterogeneity among migrants and some evolving 'new' migrant types alongside more traditional labour migrants. We show how these types are associated with differences in pre-migration human capital, region of origin and employment experience and with post-migration social and subjective integration in receiving societies.
Keywords: 330